Strategy Managemen of Strengthening Character Education Through Network and Outside Learning - Lina Sukanti (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to understand the management of character education strengthening strategies through online and offline learning. Qualitative methods through documentation studies, and observations at Madrasah Tsanawiah Al-Adzkar to find existing phenomena. interviews with interested informants. The results of the study are: (1). Planning with mapping of learning implementation policies (2). Coordination of the person in charge of the program in improving character education. carried out systematically and continuously (3). Implementation in learning is done through coaching, exemplary, habituation, and student discipline through the practice of religion, nationalism (4). Evaluation of learning through performance and learning achievement inside and outside the network.